The effectiveness of building inspection by local authority in construction process / Mohd Fazli Masbor - Masbor, Mohd Fazli (2007)
Construction process is important aspect in construction industry. This is because the construction process will produce many kind of properties like residential, industrial, commercial and etc. The properties actually will use for business, processing, resting and etc. In construction process, the party that involved giving approval is local authority. In local authority, there are many types of department that involve like building, landscape, town planning, engineering and etc. The departments must conduct building inspection for quality of building. As generally, the study is to know the effectiveness of building inspection by local authority in construction process. Furthermore, the study is to know the respondents' response in term on building inspection that conducted by local authority in construction process. Is hoped, all the collection of data can be used for rationale solutions and recommendations.